Evolution of veteran medical care support system in India - Kumar, Ashok (U.S.I Journal)
The article gives out the evolution of the veteran healthcare of the Indian armed forces post-independence till the start of the Ex-servicemen (ESM) Contributory Health Scheme (ECHS) in 2003. Post-retirement benefits are part of terms of engagement of all militaries and are an incentive, as well as reward, for serving the country in difficult circumstances risking one$1 (Bs own life. In India post-independence, from almost no medical care except for disabled category, that too for selected few disabilities, the veteran medical care has passed through various stages like authorisation of medical treatment in service hospitals, Army Group Insurance (AGI) Medical Benefit Scheme covering high cost treatment not available in service hospitals and finally to ECHS which is a cashless and capless scheme and is one of the largest and efficient healthcare system for veterans in the in world. - Reproduced s